IBM-2 دراسة خصائص نظائر إربيوم 156−162 الشفعية–شفعية باستخدام نموذج البوزونات المتفاعلة - الشفتري, نجاة سالم; بوقرين, سعاد محمد; الزوام, عياد الهادي; ناصف, دلنده محمد; القاضي, الصادق محمد (The Libyan Journal of Science, 2022)
Interacting Boson model-2 was used to calculate the energy levels of some of the even-even erbium isotopes with mass numbers 156-162. The extracted moment of inertia has been plotted versus the square of energy of the emitted photon for the experimental and computed values. The ratio of the excitation energies of the first 4+1 over the first 21+, [R =(E41+ ⁄ E21+)], is also calculated, and then compared with the three limits (SU (3), U(5) and O (6)). In addition, the E-GOS curve as a function of the spin is presented. All calculated values are compared with the available experimental data and show reasonable agreement. Whereas, the two isotopes 156Er and 158Er at low spin values had unstable gamma characteristics and with high spin values, these properties transferred to the rotational state, while the tow isotopes 160Er and 162Er showed a rotational behavior.